Bin Laden's Bald Spot : & Other Stories - Doyle, Brian, 1956 November 6-2017 May 27 (Book collections on Project MUSE., 2011)
"Welcome to the peculiar and headlong world of Brian Doyle's fiction, where the odd is happening all the time, reported upon by characters of every sort and stripe. Swirling voices and skeins of story, laugher and rage, ferocious attention to detail and sweeping nuttiness, tears and chortling--these stories will remind readers of the late giant David Foster Wallace in their straightforward accounts of anything-but-straightforward events; of modern short story pioneer Raymond Carver, a bit, in their blunt, unadorned dialogue; and of Julie Whitty, a bit, in their willingness to believe what is happening, even if it absolutely shouldn't be. Funny, piercing, unique, memorable, this is a collection of stories readers will find nearly impossible to forget"--Page 4 of cover.